(untitled) (Journal of Organizational Psychology, 2020)
This study was conducted in organisations where the implementation of change failed after repeated attempts. We were asked to look into organisational reality for the reasons why these attempts failed and what kind of other intervention strategy could be helpful in overcoming the arrested OD. The theory of organisational neglect was used as a lens for the diagnosis. In cases where signs of organisational neglect were detected a previously developed and described method for restoring normal organisational life was applied. In studying the role and the style of the OD change agents in cases of abused and neglected organisations we discovered that a successful change agent has an authoritative and demanding style. This role is different from the focus on implementing solutions as an empirical-rational strategy or coaching the process of change as a normative re-educational strategy. The change agent in abused and neglected organisations cannot work in a normal relationship with members in the organisational system because reciprocity is lost. This study shows how the change agent works and under what conditions he can be successful.